On the investigation of investment style allocation under the OCIO structure: Evidence from the Korean stock market - Jeongjoon Park; Jaewan Bae; Changjun Lee (Journal of Derivatives and Quantitative Studies: Seonmul yeon'gu (JDQS), 2021)
Given the importance of style allocation strategy under the outsourced chief investment officer (OCIO) structure, the authors examine the validity of style allocation strategies in the Korean stock market. The authors find that external investment agencies can improve performance by using newly suggested investment styles such as high dividend yield and low volatility as well as traditional styles. In addition, the authors find that the style combination strategies create economically large and statistically significant returns. Finally, empirical results indicate that factor timing strategies suggested in this study can improve the reward-to-risk ratio. In sum, the empirical findings indicate that external investment agencies under the OCIO structure can improve performance using active style allocation strategies.
Keywords: 330; Investment style; OCIO; Style combining strategy; Style timing strategy